Acknowledgments as a Window into Legal Academia - Jonathan I. Tietz; W. Nicholson Price II (Washington University Law Review, 2020)
Legal scholarship in the United States is an oddity—an institution built on student editorship, a lack of peer review, and a dramatically high proportion of solo authorship. It is often argued that this makes legal scholarship fundamentally different from scholarship in other fields, which is largely peer-reviewed by academics. We use acknowledgments in biographical footnotes from law-review articles to probe the nature of legal knowledge co-production and de facto peer review in legal literature. Using a survey of authors and editors and a textual analysis of approximately thirty thousand law-review articles from 2008 to 2017, we examined the nature of knowledge co-production and peer review in U.S. legal academia. Our results are consistent with the idea that substantial peer-review-like vetting occurs in the field. We also found evidence that both authors and editors use the information in acknowledgment footnotes as a factor in article submission and selection. Further, the characteristics of acknowledgment footnotes in articles in high-ranking law reviews differ dramatically from those in low-ranking law reviews in ways that are not simply due to differences in article quality. Finally, there are problematic gender differences in who is being acknowledged. We propose some modest changes to current practices that would help maximize transparency and minimize bias in legal scholarly networks and law-review article selection.
Keywords: Legal scholarship; Peer review; Acknowledgments; Law reviews; Scholarship publication; Article selection; Bias